2018
DOI: 10.1051/e3sconf/20186505012
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of Hazardous Waste Landfill Leachate using Photo-Fenton Process

Abstract: This study was conducted to evaluate the COD removal efficiency of Photo-Fenton oxidation process. The reagents used in the Photo-Fenton process are catalyst Fe2+ and H2O2 as oxidizing agent. A 16W UV lamp was used to carry out the experiments. All the experiments were performed in batch mode to investigate the influence of operating conditions viz., Fenton reagents dosage, molar ratio and reaction time. The maximum COD removal observed was 68% under optimum operating conditions. The operating conditions H2O2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…A previous report by Zhang et al [39] showed COD removal from landfill leachate was only 65% when hydrogen peroxide alone was applied, with the presence of ferrous ion greatly improving COD removal. Singa et al [40] observed that the maximum COD removal from landfill leachate by using photo Fenton was 68% under optimum operating conditions. Also, Singa et al [41] found that under favorable experimental conditions, maximum COD removal from landfill leachate by using Fenton process was 56.49%.…”
Section: Response Optimisation and Validation Of The Experimental Modelmentioning
confidence: 99%
“…A previous report by Zhang et al [39] showed COD removal from landfill leachate was only 65% when hydrogen peroxide alone was applied, with the presence of ferrous ion greatly improving COD removal. Singa et al [40] observed that the maximum COD removal from landfill leachate by using photo Fenton was 68% under optimum operating conditions. Also, Singa et al [41] found that under favorable experimental conditions, maximum COD removal from landfill leachate by using Fenton process was 56.49%.…”
Section: Response Optimisation and Validation Of The Experimental Modelmentioning
confidence: 99%
“…Therefore, advanced oxidation processes (AOP) such as photo-Fenton (UV/H 2 O 2 +Fe 2+ ), electro-Fenton, ozone (O 3 ) oxidation, oxidation O 3 +UV, O 3 +UV+H 2 O 2 , percarbonate oxidation or the Fenton process (H 2 O 2 +Fe 2+ ) are increasingly applied. In view of, inter alia, the wide range of application, the high non-selectivity of the • OH, and the simplicity of running the process, the Fenton process is the most popular of the AOP methods, and its main disadvantage is the generation of sediments which need to be properly managed [2,5,6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…An improvement of this conventional Fenton reaction consists in using UV radiation to reduce Fe 3+ to Fe 2+ , that is, the so-called photo-Fenton process [18][19][20][21], which enables the iron oxidation cycle to be produced again, generating more hydroxyl radicals capable of further oxidizing the remaining organic matter. As a result, it is necessary to add less iron to catalyze the process, and the production of iron sludge is minimized [22].…”
Section: Introductionmentioning
confidence: 99%
“…Different sources of UV radiation have already been assessed in their application to perform the photo-Fenton reaction, namely, high-pressure mercury-vapor immersion lamps [7,21], sunlight concentrated in compound parabolic collectors (CPC) [23,24], unconcentrated sunlight in thin film reactors [25], and light-emitting diodes (LEDs) [26]. In particular, Singa et al (2018) [21] addressed a 68% COD removal in 90 min of treatment using a 16 W high-pressure mercury-vapor immersion lamp to perform the photo-Fenton degradation of LL. Colombo et al (2019) [7] achieved an 89% COD removal in a similar photo-Fenton treatment of a sanitary LL, and the reported treatment efficiency increased up to the 98% removal of the COD when the oxidation process was combined with a posterior biological treatment.…”
Section: Introductionmentioning
confidence: 99%